Penguatan Pendidikan Agama Islam melalui Projek Penguatan Profil Pelajar Pancasila dan Profil Pelajar Rahmatan lil 'Alamin pada Madrasah Pilot Project KM-BK di Papua - Surindi; Tobroni; Faridi (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2024)
This research aims to find out how important and effective the Strengthening Pancasila and Rahmatan Lil Alamin Student Profile project is in creating Tathawur wa Ibtikar students in madrasas. A qualitative approach supported by descriptive data was used. Primary and secondary data are data components. Strengthening the Pancasila student profile and the Rahmatan Lil Alamin student profile has a significant direct and indirect impact as a positive trend in fostering the character of tathawur wa ibtikar (self-development and innovation) among students. Carried out in six stages, including (1) team formation, (2) determining the theme, (3) implementation, (4) reflection, (5) follow-up plan, and (6) project results exposure. (Tujuan dari penelitian ini adalah untuk mengetahui seberapa penting dan efektif proyek Penguatan Profil Pelajar Pancasila dan Rahmatan Lil Alamin untuk mewujudkan pelajar Tathawur wa Ibtikar di madrasah. pendekatan kualitatif yang didukung oleh data deskriptif digunakan. Data primer dan sekunder adalah komponen data. Penguatan profil pelajar Pancasila dan profil pelajar Rahmatan Lil Alamin berdampak signifikan secara langsung tak langsung sebagai tren positif dalam menumbuhkan karakter tathawur wa ibtikar (pengembangan diri dan inovasi) di kalangan pelajar. Dilakukan dalam enam tahapan meliputi : (1) Pembentukan Tim, (2) Penentuan tema, (3) Pelaksanaan, (4) Refleksi, (5) Rencana Tindak Lanjut, dan (6) Expo hasil Projek.)